28 Οκτωβρίου 1940 ; ; Ο χορός του Ζαλόγγου ; ; Σκλαβωμένα Χριστούγεννα ; ; Η πρωτοχρονιά της Μαρούλας ; ; Αγία Λαύρα / Γιάννη Β. Ιωαννίδη - Ιωαννίδης, Γιάννης Β. (Παπαδημητρίου, 2015)
ΑΚΑΔΗΜΙΑ ΡΟΔΟΥ, 2004-06